Predictive Value of the Respiratory Variation in Inferior Vena Cava Diameter for Ventilated Children With Septic Shock - Xiong, Zihong; Zhang, Guoying; Zhou, Qin; Lu, Bing; Zheng, Xuemei; Wu, Mengjun; Qu, Yi (Frontiers in Pediatrics, 2022)
Objectives: This study aimed to investigate the predictive utility of respiratory variations of inferior vena cava diameters on fluid responsiveness in children with septic shock. Design: A prospective observational single-center study. Setting: A pediatric intensive care unit in a tertiary hospital in china. Participants: Patients with sepsis shock who require invasive mechanical ventilation were recruited between 1st December 2017 to 1st November 2021 Interventions and Measurements: Volume expansion (VE) was induced by a 30 minute infusion of 20 ml/kg normal saline. Hemodynamics indexes were obtained through bedside transthoracic echocardiography (TTE) measurement and calculation. Results: 86 patients were enrolled in this study, among them, 45 patients (52.3%) were considered to be nonresponders (NR), with an increase in stroke volume variation (SVV) less than 15% after VE. Multivariate logistic analysis showed that △IVC ( OR =1.615, 95% CI 1.092-2.215, p=0.012) was the significant predictors associated with the fluid responsiveness. The area under the ROC of ΔIVC was 0.922 (95% CI: 0.829-1.000, p < 0.01), and the cutoff value of ΔIVC used to predict fluid responsiveness was 28.5%, with a sensitivity and specificity of 95.4% and 68.5%, respectively. Conclusions: The ΔIVC was found to have a potential value in predicting fluid responsiveness in mechanically ventilated children with septic shock. Key Words: echocardiography; fluid responsiveness; hemodynamic; inferior vena cava; sepsis shock; children